2020
DOI: 10.1007/s00238-020-01626-y
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center, retrospective, preliminary observational study to assess the safety of BellaGel® after augmentation mammaplasty

Abstract: Background BellaGel® is the only cohesive silicone gel-filled breast implant from a Korean manufacturer, and it was first developed in 2005. It was approved by the CE in 2008, thus becoming the first Asian breast implant available in the EU. We conducted this study to assess the safety of BellaGel® in patients receiving augmentation mammaplasty. Methods We evaluated a consecutive series of 239 patients (478 breasts) who received esthetic augmentation mammaplasty using the BellaGel® (round smooth, round texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…From this context, the BellaGel® (HansBiomed Co. Ltd., Seoul, Korea) is known as a silicone gel-filled breast implant that best fits to Korean women [13]. Its short-term safety has been well described in the literature, which is in agreement with 4-and 6-year interim results of a 10-year prospective cohort study [13][14][15][16]. The BellaGel® SmoothFine is the BellaGel® implant with a microtextured surface; it is equipped with softness as well as a refined, smooth surface with a roughness of 5.96 µm, which is a different feature from traditional smooth surface, according to the International Organization for Standardization (ISO) 14607 Annex H Test for surface characteristics (Figure 1).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…From this context, the BellaGel® (HansBiomed Co. Ltd., Seoul, Korea) is known as a silicone gel-filled breast implant that best fits to Korean women [13]. Its short-term safety has been well described in the literature, which is in agreement with 4-and 6-year interim results of a 10-year prospective cohort study [13][14][15][16]. The BellaGel® SmoothFine is the BellaGel® implant with a microtextured surface; it is equipped with softness as well as a refined, smooth surface with a roughness of 5.96 µm, which is a different feature from traditional smooth surface, according to the International Organization for Standardization (ISO) 14607 Annex H Test for surface characteristics (Figure 1).…”
Section: Introductionmentioning
confidence: 60%
“…Of these, CC occurred at an incidence of 8.8%. This is noteworthy because manufacturer-sponsored retrospective studies have shown incidences of 0.0% (0/239), 0.6% (1/78) and 1.6% (10/621) in patients receiving the BellaGel® implants including the BellaGel® SmoothFine [14,19,20]. Interestingly, another manufacturer-sponsored experimental study compared the vulnerability to CC based on surface properties between the BellaGel® implants, including the BellaGel® SmoothFine, and the Motiva Ergonomix TM SilkSurface (Establishment Labs Holdings Inc., Alajuela, Costa Rica), thus drawing conclusions that the BellaGel® SmoothFine was the least vulnerable to CC of the sample devices [18].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, they are covered with five layers except for anatomical devices covered with six layers [25]. The BellaGel ® was first developed in 2005 and then approved by the CE in 2008; it has become commercially available in 30 countries worldwide [26]. Previous studies have described the efficacy and safety of the BellaGel ® [24][25][26][27][28][29].…”
Section: The Manufacturer's Description Of the Bellagel ® Breast Implantsmentioning
confidence: 99%
“…The BellaGel  implants, including the BellaGel  SmoothFine, have been exported to 30 countries worldwide since they were first developed in 2005 [9]. It is noteworthy that their efficacy and safety have been established through evidence-based studies [8][9][10][11][12]. As recently described, it was found to be more excellent than its competitors in Korea [11].…”
Section: Introductionmentioning
confidence: 99%